Evaluasi Kualitas Konten Website Republika Online Berdasarkan Metode Global Quality Evaluation - Fitri Yanti Br Ginting; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The purpose of this paper is to evaluate the quality of the website global methods based on Online Republika quality evaluation, namely assessing the intrinsic variables, operational, contextual and representational. In addition, the study also aims to provide recommendations to improve the quality of the website Online from Republika fourth assessment variables above. Global quality evaluation is a fundamental concept to evaluate the quality of the content of the website consists of four variables that have been mentioned above. The sample used i.e. based on the selection of most of the population of visitors who access the website Republika Online. Data retrieval is done by way of disseminating a questionnaire on the user, then the data will be processed and analyzed using descriptive statistics. The result of the evaluation of the quality of the content of the website of Republika Online on intrinsic variables have a percentage of 69.49% that is located at a high category. On operational variables have a percentage of 72.10% that is located at a high category. Contextual variables have percentage 71.44% that is located at a high category. And on a variable percentage of 61.32% have representational i.e. are on a high category. However, the four variables still there are some charge indicators will still require improvement.